Demokratiebildung in Verfahren der Qualitätsentwicklung in Kitas: Eine Dokumentenanalyse Zur Stellung von Partizipation, Kinderrechten, Diversität, Diskriminierungskritik und Inklusion in der kindheitspädagogischen Qualitätslandschaft - Trần, Hoa Mai (Verlag Barbara Budrich, 2024)
Participation, children's rights, diversity and inclusion - empty buzzwords or part of democracy building in German day care centres? The author empirically examines 21 quality procedures in the field of childcare and demonstrates that there is a need for action in the quality discourse. This is especially true with regard to a discrimination-critical and diversity-sensitive orientation and in prioritising democracy building and child participation as central organisational tasks.